Optimalisasi Sistem Informasi Penjualan Berbasis Android Sebagai Media Promosi produk Cemilan Khas sumatera Barat Di HDD Snack menggunakan metode waterfall - Refli Noviardi; Yeviki Maisyah Putra; Nurmaliana Pohan (Prodi Sistem Informasi Universitas Dharma Andalas, 2023)
Pandemic covid 19 has spread all over the world , it made every sector stope, especially economic sector dan touristm sector, in every country in the word, after pandemic ,every country make their own policy to make their country not fall into recession, not even indonesia , the government want everyone can make a solution to make indonesian economy can growe and better before pandemic , one of solution are to develope any ideas with technologi , HDD snack is one of little company who’s affected og pandemic, this company everyday producting a traditional sncak form west sumatera, cause of pandemic thei can produce their product thereatened with bangkrupcy. And now we want make a study to hel this company to promote their product by using the technology , hdd snack not only can promote their product with traditional way ,but they can promote thei product in internet wit make a media promote like a website. It can increase their customer. In the future